Hubungan Kompetensi Pedagogik dan Supervisi Akademik dengan Kinerja Guru SMA Neger di Kota Dobo Kabupaten Kepulauan Aru - Fransina M. Faubun; G.T. Ratumanan; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to: 1). Describing the pedagogic competence of State High School teachers in Dobo City, Aru Islands Regency. 2) Describe the academic supervision of State High School teachers in Dobo City, Aru Islands Regency. 3). Describe the performance of State High School teachers in Dobo City, Aru Islands Regency. 4). To find out whether there is a relationship between pedagogic competence and the performance of State High School teachers in Dobo City, Aru Islands Regency. 5). To find out whether there is a relationship between academic supervision and the performance of State High School teachers in Dobo City, Aru Islands Regency. 6). To find out whether there is a relationship between pedagogic competence and academic supervision simultaneously with the performance of State High School teachers in Aru Islands Regency. The research population was state high schools in the city of Dobo, namely SMA Negeri 1 Kepuluan Aru and SMA Negeri 3 Aru Islands with a total of 56 teachers as respondents. The research results found a positive and significant relationship between pedagogical competence and teacher performance with a correlation value of 0.428 and a significance value of 0.001. There is a positive and significant relationship between academic supervision and teacher performance with a correlation value of 0.382 and a significance value of 0.004. There is a positive and significant relationship between pedagogical competence and academic supervision together with teacher performance with a correlation value of 0.510 and a significance value of 0.000